ANALISIS KARAKTER PROFIL PELAJAR PANCASILA DI RUMAH PADA KELAS 4 SDN SAWAH BESAR 01 - Nur Maulidasari; Filia Prima Atharina; Mira Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to see how the implementation of the Pancasila student profile program in the independent curriculum and to find out whether it has an impact on the formation of student character at home in class 4A students at SDN Sawah Besar 01. This research uses a triangulation research method, namely the researcher distributes questionnaires filled out by students, documentation containing Pancasila student profile activities implemented at home and journal filling accompanied by parents at home. Data collection techniques in this study used questionnaires and journals. Data analysis through the process of data reduction, data display, and verification. The sampling technique used purposive sampling. The results of this study indicate that all of the Pancasila Student Profile characters have been applied at home as much as 71% of the number of class 4A students, namely 28 students, meaning as many as 20 students who apply everything, the number of students who apply the Pancasila student profile characters is only partially as much as 18%, meaning as many as 5 students who apply some and students who apply only a little as much as 11%, meaning as many as 3 students apply it. The results of this study can be used as a teacher as an evaluation of learning in schools related to the cultivation of the Pancasila student profile character which is very strong so that it is implemented by students at home.